MITIGATING INFLATION VIA ISLAMIC FINANCE & ISLAMIC SOCIAL FINANCE : THE CASE OF MALAYSIA - Mohsin, Magda Ismail A. Mohsin (I-iECONS e-proceedings, 2023)
The aim of this paper is to highlight the current practices of Islamic Finance IF and Islamic Social Finance ISF in mitigating inflation in Malaysia. This study used a descriptive qualitative method collected from secondary data consisting of documents relate to the subject matter at hand. The type of documents used are published articles, reports, journals, and websites. Islamic Finance IF & Islamic Social Finance ISF offers various financial products that help to eliminate riba/interest from society, circulate the wealth from the have to the have not in an ethical approach, hence, stabilizing prices and mitigating inflation. This paper is a conceptual study which does not aim to empirically examine the issues but provide successful cases to be adopted by Muslim countries in eliminating riba/interest from their societies and hence mitigating inflation. This paper dose not only presents the Islamic approach in mitigating inflation, but it provides current practical cases in achieving so. So, this paper will be of great interest to students/researchers/economist/financial institutions and policy makers. Islamic Finance IF & Islamic Social Finance ISF are based on principles deduced from the Quran and Sunnah and which need to be implemented in Muslim societies not only for mitigating inflation but for achieving social justice for all.